Modified compact tension specimen for experiments on cement based materials: comparison of calibration curves from 2D and 3D numerical solutions (Fracture and Structural Integrity, 2016)
The evaluation of fracture mechanics parameters of materials has become very important part of considering the condition of older constructions as well as properties of newly developed materials. This contribution focuses on a numerical simulation and a calculation of fracture mechanical properties of modified compact tension test configuration. It is possible to prepare the specimens used for this test very easily from a drilled core or from specimens used for cylindrical compression test. The focus of contribution is to compare selected outputs from numerical solution of 2D (plane strain conditions) with 3D models. Particularly, the determination of the influence of 2D and 3D model on the calibration curves for selected fracture mechanics parameters is of interest. Finite element software ANSYS was used for the numerical analysis.
Keywords: Stress Intensity Factor; COD; CMOD; Biaxiality Factor; Modified Compact Tension Test; Fracture Mechanics of Concrete